Rate of Perceived Exertion Based on Repetitions in Reserve Versus Percentage of One-Repetition Maximum for Resistance Training Prescription in Cardiac Rehabilitation: A Pilot Study - Alessandro Gismondi; Ferdinando Iellamo; Giuseppe Caminiti; Barbara Sposato; Emanuele Gregorace; Valentino D’Antoni; Deborah Di Biasio; Sara Vadalà; Alessio Franchini; Annalisa Mancuso; Valentina Morsella; Maurizio Volterrani (Journal of Cardiovascular Development and Disease)
The aims of this study were to assess the efficacy of the rate of perceived exertion (RPE) scale based on the number of repetitions in reserve (RIR) before exhaustion for the prescription of resistance training in cardiac rehabilitation and to compare it to the percentage of estimated one-repetition maximum (1RM) prescription method. Sixteen male patients (age 60 ± 8) with history of coronary artery disease were randomly assigned to two resistance training rehabilitation protocols lasting nine weeks and consisting of three sessions per week, with the same exercise selection, number of sets and repetitions, and rest periods, but different load prescription method (RPE vs. %1RM). Patients’ strength was evaluated pre- and post-intervention. Patients in the RPE group showed significant increases in strength across all the exercises of the protocol (leg press 24.25 ± 17.07 kg; chest press 7.25 ± 3.41 kg; seated row 13.88 ± 7.57 kg; leg extension 14.24 ± 4.53 kg; shoulder press 5.75 ± 4.06 kg; lat pulldown 7.50 ± 4.66 kg). Post-intervention between-group analysis showed no differences in strength gains (leg press p = 0.955; chest press p = 0.965; seated row p = 0.763; leg extension p = 0.565; shoulder press p = 0.868; lat pulldown p = 0.780) and trivial effect sizes (ES) for one prescription method over the other (leg press ES = −0.03; chest press ES = 0.00; seated row ES = 0.10; leg extension ES = −0.29; shoulder press ES = 0.18; lat pulldown ES = 0.05). RPE based on RIR seems to be an effective prescription method for resistance training in cardiac rehabilitation, showing similar efficacy to the standardized practice of percentage of 1RM.